Quality of Mobile Apps for Child Development Support: Search in App Stores and Content Analysis - Akeiylah DeWitt; Julie Kientz; Kendra Liljenquist (JMIR Publications, 2022)
BackgroundFollowing increases in smartphone access, more parents seek parenting advice through internet sources, including blogs, web-based forums, or mobile apps. However, identifying quality apps (ones that respond to the diverse experiences of families) for guidance on child development can be challenging. ObjectiveThis review of mobile health apps aimed to document the landscape, design, and content of apps in the United States available to parents as they promote their child's developmental health. MethodsTo understand the availability and quality of apps for early childhood health promotion, we completed a content analysis of apps in 2 major app stores (Google Play and Apple App stores). ResultsWe found that most apps do not provide tailored experiences to parents, including cultural considerations, and instead promote generic guidance that may be useful to parents in some contexts. We discuss the need for an evaluative framework to assess apps aimed to support parents on child development topics. ConclusionsFuture work is needed on how to support designers in this area, specifically related to avoiding potential burdens on users and providing culturally informed and equity-driven experiences.